2005
DOI: 10.1007/s10517-005-0372-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Verapamil and Amiodarone on Sympathoadrenal System and Balance of Excitatory and Inhibitory Amino Acids in Rat Medulla Oblongata

Abstract: Local injection of verapamil into ventrolateral region of the medulla oblongata triggered the release of epinephrine. Verapamil increased the total content of norepinephrine and epinephrine by 560% and decreased the content of serotonin by 46%. Verapamil had no effect on norepinephrine/epinephrine and norepinephrine/(norepinephrine+epinephrine) ratios in normal rats. Blockade of K+-channels in the medulla oblongata by local injection of 0.001 mg amiodarone did not change the levels of epinephrine and norepinep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…This drug is highly lipid-soluble, and had been shown to pass into the brain (Wyss et al, 1990;Riva et al, 1982) and also to increase the concentrations of GABA and glycine (Turovaya et al, 2005); thus we may speculate that this drug had shown synergic effect with pentobarbital. Ohtsuka et al(2006) reported that barbiturates used as anticonvulsant drug at high concentrations but not at clinically relevant concentrations inhibited ATP-sensitive K + channel (K ATP ) channels activated by intracellular ATP depletion in rat substantia nigra, and Holmes et al(2000) reported that amiodarone inhibited the K ATP channels.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This drug is highly lipid-soluble, and had been shown to pass into the brain (Wyss et al, 1990;Riva et al, 1982) and also to increase the concentrations of GABA and glycine (Turovaya et al, 2005); thus we may speculate that this drug had shown synergic effect with pentobarbital. Ohtsuka et al(2006) reported that barbiturates used as anticonvulsant drug at high concentrations but not at clinically relevant concentrations inhibited ATP-sensitive K + channel (K ATP ) channels activated by intracellular ATP depletion in rat substantia nigra, and Holmes et al(2000) reported that amiodarone inhibited the K ATP channels.…”
Section: Discussionmentioning
confidence: 93%
“…Following PTZ-induced seizures, Takemiya et al(2003) showed that COX-2 had induced prostaglandins and had enhanced levels of prostaglandin D 2 and prostaglandin E 2 . In addition, Turovaya et al(2005) reported that amiodarone had increased the concentrations of inhibitory GABA and glycine and had decreased those of excitatory aspartate and glutamate in rat medulla oblongata. In our study, the anticonvulsant effect of amiodarone in PTZ-induced seizures may be partially due to blockage of ion channels (Na + , K + and Ca 2+ )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13][14][15][16][17][18] One pathophysiologic theory of damage is mechanical or biochemical decrease of axoplasmic flow due to deposition of lamellar bodies within optic nerve axons. 3 Experimental studies suggest potential neurotoxic effect of amiodarone, [19][20][21][22][23] and in 2016, a novel potential pathomechanism was reported by Liao et al 24 This study showed that amiodarone induced apoptosis of RGC-5 cells (a clonal, retinal, neuronal cell line, established as a model to study glaucomatous damage in vitro) via inhibiting the phosphoinositide 3-kinase (PI3K)/Akt/FoxO3a pathway. However, overall, it is still controversial whether amiodarone-associated optic neuropathy (AAON) is a mere drug related condition or whether it represents a form of non-arteritic ischaemic neuropathy (NAION) in a high-risk cardiovascular population.…”
Section: Introductionmentioning
confidence: 99%
“…В результате экспериментальных исследований установлено, что токсичность амиодарона обусловлена блокированием Na + , K + или Ca 2+ -каналов [25] с последующим увеличением уровней L-допа и допамина, что приводит к изменению соотношения нейроактивных аминокислот и ингибиторных трансмиттеров [26]. Нейротоксичность возникает вследствие ингибирования активности протеинкиназы С и кальмодулин-регулирующих ферментов, модулирующих вне-и внутриклеточные сигналы через мембрану нейронов [27].…”
unclassified